Before the Performance: contributions of speculative pragmatism to the sociology of art - Felix Martins , Daniela (Revista Brasileira de Estudos da Presença, 2023)
The aim of this paper is to analyze the main aspects that constitute the performance experience, as well as to examine the contributions of speculative-pragmatism to the renewal of the field of sociology of art. The text is structured in three parts: 1) a contextualization of the work within the scope of the research project Protocols for the Musealization of Performative Actions in Public Art Museums and its problematic from the sociological point of view; 2) a definition of the concept of experience; 3) verification of the analytical yield of this concept for research in performance arts. As a main conclusion, the text sought to systematize the ways in which pragmatic-speculative sociology may provide access to the complex networks of actors and social practices involved in contemporary artistic production.